A study on antiproliferative activity of methanolic extract of Nephelium lappaceum peel towards selected cancer cell lines - Sul'ain, Mohd Dasuki (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Nephelium lappaceum which belongs to family Sapindaceae is subtropical and tropical native fruit of the Southeast Asia but unknown in the United States (Ong et al., 1998). Nephelium lappaceum is known as rambutan in Malaysia where the fruit is generally consumed fresh and industrially processed to juices, jams and jellies. However, the seeds and peels of Nephe/ium /appaceum are often treated as a waste. Some phytochemical constituent such as geraniin (Palanisamy et al., 2010), ascorbic acid and vitamin c (Wall, 2006) and volatile compounds (Ong et al., 1998) of Nephelium lappaceum had been isolated from the fruits and peels. Studies on Nephe/ium lappaceum showed it to pose some therapeutic activities such as antioxidant (Palanisamy et al., 2008), antibacterial (Thitilertdecha et a!., 2008), antivirus (Nawawi, 1999) and anti-hyperglycemic (Palanisamy et al., 2010). In this study, Nephe/ium lappaceum was extracted using a different organic solvents and were tested for antiproliferative effect on several cancer cell lines using methylene blue assay. The purpose of this study was to determine the antiproliferative activity of organic extracts of Nephelium lappaceum peels on selected cancer cell lines.